A study of speech compression algorithms for Voice over IP. - Montminy, Christian. (University of Ottawa (Canada), 2000)
Voice over IP (VoIP), the transmission of voice over an IP network, is gaining much momentum in the industry. Its benefits over conventional telephony are numerous, but the impairments present on an IP network make implementing such a system quite a challenge. In this thesis, Voice over IP (VoIP) will be studied with a particular emphasis on the speech compression algorithms used in such a system. The desired characteristics of a speech compression algorithm for VoIP will be analyzed. These characteristics will then be used to judge how appropriate are some existing standards of speech compression algorithms for VoIP. A promising speech compression algorithm resulting from this analysis, ITU-T G.729A, will be used to analyze its ability to recover from packet loss since this is one of the main impairments of an IP network. Finally, a novel method to improve the performance of this algorithm in presence of packet loss will be described with results.
Keywords: Engineering, Electronics and Electrical.